Obituary-Donald Henry Colless 1922–2012 - Yeates, David K.; Cranston, Peter S. (Zootaxa, 2013)
Donald Henry Colless (24 August 1922–16 February 2012) was a taxonomist at the Australian National Insect Collection (ANIC) from 1960 until his retirement in 1987. He continued working in ANIC as an Honorary Fellow until his death in 2012. Don’s main scientific interests were in the taxonomy and biology of true flies, and in the theory of phylogenetic reconstruction and classification. Don was trained in entomology at the University of Sydney, and spent nearly two de-cades of his early career in Asia studying mosquitoes and disease transmission, first in the Army during the Second World War in New Guinea and Borneo (1942–45), then after the war in North Borneo (1947–1952) and as a lecturer in the De-partment of Parasitology at the University of Malaya (1952–1960) in Singapore. We list the 127 scientific papers and book chapters that Don published during his scientific career that spanned 64 years. Six of these papers were published in the prestigious international journal Nature, and he was Chief Curator of the ANIC from 1971–1977. Don had extremely broad taxonomic interests, publishing on the taxonomy of 18 families of Diptera that spanned the phylogenetic breadth of the order. He described as new to science the fly families Perissommatidae and Axiniidae, thirteen new genera and over 120 species and, with David McAlpine, authored the Diptera chapters in both editions of The Insects of Australia (Mel-bourne University Press, 1970 and 1991). He published a number of influential critiques of cladistic theory in the 1960’s and 1970’s, and advocated a phenetic approach to the discovery of taxonomic groups, and phylogenetic reconstruction.